Prediksi Rating Factor Jembatan Komposit dengan Dua Variabel Kerusakan Menggunakan Artificial Neural Network - Aminullah, Akhmad; Rahmad, Nurbetha H; Yudhistira, Angga T. (2014)
Nowadays Artificial Intelegence (AI) has developed for many bridge deterioration model. The learning ability of AI promising reliable result in forecasting and modelling even in the existence of non-linear complex relationship. Furthermore, user friendly AI tools provided by today’s software makes AI methods more attractive. In this study one of Ai method, Artificial Neural Network (ANN) are used to develop models to predict bridge ratting factor using current geometry, age, traffic load, and structural attributes as variables. Data is acquired from site investigation and structural modelling that has implemented before. ANN model provided reliable result in bridge ratting factor deterioration using Indonesian bridge data.